Efficacy of crizotinib retreatment after crizotinib-related interstitial lung disease in a patient with ROS1-rearranged advanced lung adenocarcinoma: A case report and potential crizotinib retreatment strategy - Ryu, Woo Kyung; Cha, Hyungkeun; Park, Mi Hwa; Kim, Jung Soo; Choi, Jeong-Seok; Kim, Lucia; Lee, Kyung-Hee; Nam, Hae-Seong (Frontiers in Oncology, 2022)
Crizotinib is an oral selective small-molecular tyrosine kinase inhibitor (TKI) that suppress the activity of anaplastic lymphoma kinase (ALK) and ROS1 kinases, as well as mesenchymal-epithelial transition. The cumulative clinical trials in patients with advanced ALK- or ROS1-rearrangement NSCLC indicate that crizotinib has significant antitumor activity and a tolerable safety profile, with mild or moderate adverse events of visual disorders, diarrhea, nausea, and vomiting. As with other TKIs, however, the occurrence of crizotinib-related interstitial lung disease (crizotinib-ILD) remains a major clinical dilemma that can lead to the permanent discontinuation of TKI during cancer treatment. When there is no suitable alternative therapy for patients who develop crizotinib-ILD, some clinicians have reported successful crizotinib retreatment in cases of ALK-rearrangement NSCLC. Unfortunately, there are no specific guidelines for the treatment or retreatment of TKI-related ILD. We herein report the first successful crizotinib retreatment after crizotinib-ILD in a patient with ROS1-rearranged NSCLC, and suggest a retreatment strategy after crizotinib-ILD based on a literature review.